Efficacy of alpha-lipoic acid for the treatment of carpal tunnel syndrome: A systematic review and meta-analysis of randomized controlled trial studies - Harvey Sudharta, Glenardi Halim, Rizaldy Taslim Pinzon, Jimmy Fransisco Abadinta Barus (Journal of Applied Pharmaceutical Science, 2024)
Surgical intervention for carpal tunnel syndrome (CTS) has proven to relieve symptoms significantly, but some patients may experience persistent postoperative symptoms, requiring a multitargeted approach. Alpha-lipoic acid (ALA) has demonstrated promising results in terms of anti-inflammation, neuroprotection, and neuroregeneration. This systematic review and meta-analysis were carried out with multiple electronic databases, such as PubMed, ScienceDirect, EBSCO, ProQuest, and Google Scholar from inception until March 28, 2023. Studies were included if they met the eligibility criteria. This study was reported following the preferred reporting items for systematic reviews and meta-analyses guideline. Standardized mean differences/mean differences with a confidence interval of 95% were used to determine ALA’s efficacy in treating CTS. A total of six randomized clinical trial studies (RCTs) were included in the systematic review, and five RCTs were included in the final meta-analysis. Most subjects were females aged 45–69 years. Boston Carpal Tunnel Questionnaire score, median motor nerve distal latency (MDL), and Visual Analog Scale (VAS) all showed significant improvement in the ALA group. There was no significant improvement in median sensory nerve conduction. In conclusion, postoperative ALA supplementation may be beneficial in improving the clinical function of CTS. ALA improved MDL but did not affect sensory nerve conduction velocity. Further studies are required to further elucidate this conclusion.
Keywords: Alpha lipoic acid, ALA, carpal tunnel syndrome, CTS, adjuvant, therapeutics, combined modality therapy